Reflecting on practical experiences with school and teaching.: The final assignment in the social and educational sciences in the Master’s programme for secondary level I teaching at the University of Teacher Education Lucerne - Cocard, Yves; Tettenborn, Annette (Swiss Journal of Educational Research, 2021)
At the University of Teacher Education Lucerne (Switzerland), prospective teachers who intend to teach at secondary schools complete their studies in social and educational sciences with a written assignment. In this final paper, teachers to-be are expected to reflect in a methodical and systematic way on school- and teaching-related situations that occurred during their internships. The reflective processes are guided by the phases and categories that form part of the framework model EDAMA (Aeppli & Lötscher, 2016), a model specifically designed for reflection purposes. In our contribution, we present longer passages from one assignment that serves as example to illustrate how a student teacher experienced a significant situation in his internship and in what way he analyses and evaluates this situation in accordance with the model. In order to assess the quality of the student teacher‘s reflections, the lecturers too draw on criteria that refer to the model.